“llusions of Absence:” Disappearances, Displacements, and the Limits of Responsibility in The Winter's Tale and The Remains of the Day - Bruce, Susan (Intermédialités / Intermediality)

(untitled) (Centre de recherche sur l'intermédialité, 2007)
This essay takes for its subject the disappearances of characters from two different texts: Ruth and Sarah, the Jewish servant girls expelled from Darlington Hall in Kazuo Ishiguro's The Remains of the Day, and Mamillius, the heir to Leontes, King of Sicilia, who dies in Act 2 of Shakespeare's The Winter's Tale. These characters are so absolutely erased from the texts in which they so briefly appear that it is as if they have been “disappeared” by them: they become, I argue, quite literally notable by their absence. Denied a presence in the texts, however, such personages do not, as might be expected, simply disappear. They won't quite go away; rather, they lodge instead in the mind of the reader, the pretence of their absence troubling the illusions of closure with which the texts both end. This displacement from textual to mental medium, I maintain, entails ethical consequences for the reader or audience. Unable to lay these ghosts to rest in the way in which the texts' protagonists appear to be able to do, the reader is forced to confront issues of responsibility not by what is present in the text, but by what is not there, or not there any longer.